Optimization of Irrigation Parameters of Peanut Under Mulched Drip Irrigation in Xinjiang Based on Yield and Water Use Efficiency - Yuchao Zhang; Shaofei Li; Weimin Cui; Yang Gao; Zhuanyun Si; Haiming Li; Junwei Chen; Jianshu Dong; Qiang Li; Xiaojun Shen; Xiaopei Zhang (Agronomy)
To optimize water–nitrogen management for mulched drip-irrigated peanuts in Xinjiang, a three-season field experiment was conducted to assess the impacts of drip irrigation rates and water–nitrogen coupling on peanut growth, yield, quality, and water–nitrogen use efficiency. Two irrigation accounts (30 and 37.5 mm, denoted as W1 and W2), three nitrogen application levels (half nitrogen application and conventional nitrogen application, denoted as N1 and N2), and a control treatment (CK) without nitrogen application, and two drip discharge rates (3.0 and 6.0 L h−1, denoted as Q1 and Q2) were utilized for a total of five treatments per year, and the experiment was repeated three times. The results demonstrated that the irrigation and fertilization parameters of the W2N1Q2 treatment could significantly improve peanut growth, yield, quality, and water–nitrogen use efficiency, achieving optimal values for all measured indicators. Compared with the control (W2N0Q1), the main stem height increased by 9.59% and 13.13%, the aboveground biomass increased by 6.32% and 34.67%, the yield increased by 26.69% and 20.97% (p < 0.01), the water use efficiency increased by 27.08% and 16.33%, the nitrogen partial factor productivity values were 47.39 and 77.00 kg kg−1, the protein content increased by 3.99% and 4.63%, and the oil content increased by 1.68% and 8.53%, respectively. A PCA was performed using five key performance indicators (yield, protein content, oil content, water use efficiency, and nitrogen partial factor productivity) to evaluate different treatment combinations. The W2N1Q2 treatment obtained the highest composite score, indicating its overall superior performance among all treatments. Therefore, under the conditions of this experiment, the irrigation and nitrogen application parameters for achieving both a high yield and quality of peanuts under mulched drip irrigation in Xinjiang were determined to be W2N1Q2 treatment (irrigation account of 37.5 mm, nitrogen application of 118 kg ha−1, and drip discharge of 6.0 L h−1). This optimized combination brings three key advantages to water-scarce regions: (1) maximizing yield water use efficiency through precise irrigation scheduling; (2) balanced nutrient management to prevent nitrogen wastage; and (3) providing a key technological reference for agricultural production in Xinjiang and other similar ecological zones.